Estimating nonlinear intergenerational income mobility with correlation curves - William Nilsson (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
A correlation curve is introduced as a tool to study the degree of intergenerational income mobility, i.e. how income status is related between parents and adult child. The method overcomes the shortcomings of the elasticity of children's income with respect to parents' income (i.e. its sensitiveness to different dispersion among the generations) and the correlation coefficient (i.e. its inability to capture nonlinearities). The method is particularly suitable for comparative studies and in this study labour earnings are compared to disposable income. The correlation between the parental income and the child's adult disposable income becomes stronger for higher percentiles in the income distribution of the parents. Above the median the correlation is found to be stronger than for labour earnings. Interestingly, the elasticity is higher for labour earnings for most part of the distribution and complementing the elasticity with correlation curves provides a much more complete picture of the intergenerational income mobility.
http://dx.doi.org/10.7910/DVN/GD0PSY
Keywords: C14; D63; J62; 330; intergenerational mobility; nonlinear; nonparametric; correlation curve